Increasing the Selling Power of Bananas by Processing Them Into "Banana Crispy" - Putri, Melinia Apritia; Missalam, Talam; Fadlur Rohman, Rivan; Badrussalam, Ria Rizky Fernanda; Khaerun Nisa, Rintan; Tauhid, Rijal; Nurjanah, Rahmah; Nurhasanah, Neni; Alamsyah, Nasya; Lestari, Yusi Dwi (AbdimasMu UMTAS, 2023)
Bolang Village, Dusun Sukahurip is one of the villages in Cilacap Regency, where the average population earns a living by farming and gardening. One of the most abundant Natural Resources in Bolang Village, Dusun Sukahurip, is bananas. But the results of the bananas that can be obtained here have minimal selling value if sold fresh. To increase the selling value of these bananas, it is necessary to innovate banana processing to become a useful advantage. The method used in this service is by conducting seminars and entrepreneurship discussions as well as practical training on making "banana crispy". The purpose of implementing this activity is so that the community can have additional income with the hope that the people of Bolang Village, Sukahurip Hamlet, can prosper.